Arthroscopic Ankle Fusion: Are Results Reproducible Irrespective Of Pre-Operative Coronal Joint Deformity?. Issue 1 (19th August 2016) - Schmid, Timo; Penner, Murray J.; Krause, Fabian; Younger, Alastair S.; Wing, Kevin; Veljkovic, Andrea
Category: Ankle Arthritis Introduction/Purpose: Arthroscopic ankle arthrodesis (AAA) has been shown to result in reduced postoperative stay and better short-term outcome than open ankle arthrodesis. Coronal ankle joint deformity often is considered a contraindication for AAA. The aim of this study was to examine whether a preoperative coronal deformity influenced the midterm outcome after AAA for end-stage ankle arthritis. Methods: The Canadian Orthopaedic Foot and Ankle Society (COFAS) database prospectively collects data about the outcome of patients after surgical treatment of end-stage ankle arthritis. The database yielded 98 patients who had isolated ankle arthrodesis at the University of British Columbia between 2005 and 2013. The cohort consisted of 66 men and 32 women who had 62 arthroscopic and 38 open arthrodesis. The preoperative coronal deformity was measured using the tibiotalar angle (between a line perpendicular to the anatomical axis of the tibia and the proximal talar surface) and the tibial plafond angle (between a line perpendicular to the tibial axis and the distal tibial surface) on weight-bearing x-rays. Primary outcome measure was the COFAS Ankle Arthritis Scale (COFAS-AAS) at final follow-up. Secondary outcome measures were the reduction of the COFAS-AAS (ΔCOFAS-AAS) and the medial tibiotalar surface angle (between the anatomical axis and the proximal talar surface) at final follow-up. Results: The tibiotalar angle was lower in the arthroscopic than in the open group (8.2°±7.0 vs. 12.3°±8.2, p=.014) with similar range in both groups (0-25° vs. 0-27°). However, the tibial plafond angle (3.6°±11.4 vs. 11.4°±12.3, p< .005) and its range (0-19° vs. 0-43°) were markedly different. (Figure) The arthroscopic group scored slightly better regarding COFAS-AAS (26.0±19.8 vs. 28.8±23.6, p=.529) and ΔCOFAS-AAS (- 28.1±19.6 vs. -25.9±20.8, p= .603). Concerning patients with tibial plafond angles ≤19°, again the arthroscopic group had slightly better COFAS-AAS (26.0±19.8 vs. 28.9±12.4, p=.588) and ΔCOFAS-AAS (-28.1°±19.6 vs. -26.0°±18.5, p=.627). Regression analyses revealed no effect of tibiotalar or tibial plafond angle onto COFAS-AAS (p=.267 and p= .965) and ΔCOFAS- AAS (p=.741 and p=.392). Radiographic outcome was similar in both groups (medial tibiotalar angle 89.3°±2.2 vs. 88.1°±4.4, p=.135). Conclusion: Both, arthroscopic and open arthrodesis were associated with significant improvements in the COFAS-AAS and acceptable radiographic alignment. Former studies used the tibiotalar angle to describe preoperative coronal ankle joint deformity. In the presented study the range of the preoperative tibiotalar angle was similar in both groups, whereas all patients with tibial plafond angles ≥20° had an open arthrodesis. Therefore, the tibial plafond angle seems to better assist when deciding between arthroscopic or open arthrodesis in patients with a coronal ankle joint deformity. Within these limits preoperative coronal deformity had no influence on the outcome of arthroscopic ankle arthrodesis.